PRECISE MOSSBAUER MILLIPROBE DETERMINATION OF FERRIC IRON IN ROCK-FORMING MINERALS AND LIMITATIONS OF ELECTRON MICROPROBE ANALYSIS - Sobolev V.N.; Taylor L.A.; Snyder G.A.; Sobolev N.V.; McCammon C.A. (My University, 1999)
For estimations of P-T conditions of igneous and metamorphic rocks, Fe 3 in coexisting minerals is either assumed to be zero or is calculated from electron microprobe analyses (EMPA) based upon stoichiometry and charge balance. Geothermobarometers that involve Fe 2 -Mg 2 exchange can be significantly affected by either neglecting Fe 3 or using in-correct values. Ratios of Fe 3 /Fe in garnet and clinopyroxene measured by a Mössbauer milliprobe were compared to those calculated from EMPA of garnet and clinopyroxene from eclogite xenoliths from the Udachnaya kimberlite in Yakutia. The effects of Fe 3 contents in garnet and clinopyroxene on temperature estimations were evaluated. The following Fe 3 /Fe (in at%) values were obtained (EMPA/Mössbauer): Gt 9.4/ 6.0; 11.5/7.0; 19.4/16.0; and 24.7/15.0; Cpx 22.0/22.9; 34.2/22.0. The effects of Fe 3 in clinopyroxenes on calculated temperatures are illustrated by taking eclogitic clinopyroxene compositions and changing contents of certain elements within the range of standard de-viations for EMPA of those particular elements. Increasing Na 2 O contents from 5.67 to 5.74 wt% (2.0% relative error) would lead to increasing Fe 3 /Fe from 31.6 to 47.1%, thereby decreasing the calculated temperature from 1026 to 941 C. Various Fe 3 /Fe values for garnet and clinopyroxene were also tested for their effects on calculated tem-peratures: for clinopyroxene, T decreases with increasing Fe 3 /Fe whereas for garnet, T increases with increasing Fe 3 /Fe. This compensation effect between garnet and clino-pyroxene moderates the variation in temperature estimations of eclogites based on Fe 3 corrected vs. uncorrected microprobe analyses. Little correlation exists between EMPA-calculated and Mössbauer-measured Fe 3 /Fe values for these mantle-derived garnets and clinopyroxenes. Even a small relative error in Fe 3 may significantly change calculated temperatures of equilibration, seriously affecting petrologic interpretations. In particular, uncertainty in Fe 3 calculated from EMPA of sil-icate minerals leads to serious questions with regard to K D values obtained from natural assemblages.